At Westonci.ca, we connect you with the answers you need, thanks to our active and informed community. Join our platform to connect with experts ready to provide precise answers to your questions in different areas. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.

-6(3x+2)=-2x-5-20x-7

Sagot :

hqs454

Answer:

Step-by-step explanation:

[tex]-6(3x+2)=2x-5-20x-7[/tex]

-6 times 3x and 2 =

-18x-12=2x-5-20x-7

combined like terms on the right side

2x - 20x= -18x

-5-7= -12

-18x-12=-18x-12

this equation equals 0=0